IMPACT OF COALITION POLITICS ON INDIAN GOVERNANCE - Bishamber; Devi, Mamta (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Forming a coalition government after elections is a feature of the parliamentary system because when no party gets an absolute majority, then many political parties come together to form a coalition government. The word 'coalition' is the translation of the English word coalition. 'Coalition' is derived from the Latin language, which means 'moving forward together'. According to the dictionary, coalition means a body, individuals or states united in a union i.e. an adjustment of different parts. It describes the process of forming an agreement between different political parties. Coalition governments are usually formed when one or more parties within the legislature form a government in alliance with one or more other parties in a parliamentary election to share the duties of governance. Sometimes, such governments emerge to fill a political vacuum in representation and to guarantee political stability, especially where there is severe political fragmentation. Such governments involve forming coalition governments, in which compromise and pragmatism matter more. This is evidenced by the voting results, which culminate in the creation of a common minimum programme. The basis of governance is shared policy and programmes. But with limited interference of the core principles of the other, allowing the partners to maintain their ideological identities. Indian coalition politics is in a constantly evolving form and through flexibility can change the political partners involved in the process. These partnerships can be pre-election, which unite different interests and policy priorities, in order to form a functioning government with the capacity to achieve agreed goals. Post-election partnerships are also frequent in India. Pre-poll alliances are considered more favourable as the parties entering into the alliance agree to go to the polls under one banner, which includes presenting a common manifesto to the voters. On the other hand, post-poll alliances emerge as a power-sharing solution when one party does not have an absolute majority to form the government and continue to rule.